KEAMANAN DOKUMEN MULTI-LAYER MENGGUNAKAN STEGANOGRAFI DAN HONEY ENCRYPTION - Gabriel Nathanael Purba; Kadek Yota Ernanda Aryanto; I Ketut Resika Arthana (Jurnal Informatika dan Teknik Elektro Terapan, 2026)
Digital transformation has increased use of digital documents vulnerable to cyber threats such as brute-force attacks and steganalysis. Conventional encryption ensures data confidentiality but provides explicit failure indicators when incorrect keys are used, potentially aiding attackers. Prior studies examined Honey Encryption and LSB steganography separately: Honey Encryption has largely focused on credential or text-based data, while LSB with cryptography has relied on conventional encryption that still exposes decryption failure indicators. This study proposes a multi-layer document security system integrating Honey Encryption and Least Significant Bit (LSB) steganography with AES-CBC, representing a novel integration of deception-based cryptography and covert data embedding within a unified framework. PDF documents are mapped into seeds using a simplified Distribution Transforming Encoder, then encrypted and embedded into PNG images using LSB. The system is evaluated through functional testing, brute-force simulation, processing time measurement, visual quality analysis using Peak Signal-to-Noise Ratio (PSNR) and Mean Square Error (MSE), and steganalysis using StegExpose. Results show the system generates structurally valid decoy documents when incorrect keys are applied, without exposing failure indicators to the user. High PSNR and low MSE values, a consequence of the small constant-size payload, indicate minimal visual distortion, while steganalysis results remain within acceptable detection thresholds.